PENGARUH IKLAN ONLINE MELALUI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN BAGI PENINGKATAN PENJUALAN PRODUK KULINER LOKAL - Adhita Maharani Dewi (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2018)
This study examined the Influence of Online advertising Via Instagram consisting of attitude towards the ad, ad recall and clik throught rates, against the decision of the purchase for the increased sales of Local Culinary Products.The purpose of this research was to describe the activity of young culinary entrepreneurs in social media that is instagram the current phenomenon of increased numbers of their accounts as well as how much influence the activity of the young culinary entrepreneurs on instagram can increase sales of local culinary products. With the right marketing activities on instagram can be beneficial against purchasing decisions so that it will enhance local culinary products. sales.This research use questionnaire as a research instrument to get the data from the consumer Pasta Resembles and Markobar1996. In this study the criteria of respondennya i.e. the respondent must as followers, and never eat the product by the number of samples planned is 200 people. Analysis tools that will be used Multiple Linear Regression is to test the influence of the dependent and independent variables.The results of the data processing has been done the third factor i.e. attitude towards the advertising, ad recall and click rates are throught to have simultaneous and partial influence against the purchasing decision. Factor Ad Recall is the most dominant factor and Factor Click Throught Rates is the factor that has the most influence diminished purchasing decisions